1986
DOI: 10.1038/321075a0
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the gene and cDNA for mammalian β-adrenergic receptor and homology with rhodopsin

Abstract: The adenylate cyclase system, which consists of a catalytic moiety and regulatory guanine nucleotide-binding proteins, provides the effector mechanism for the intracellular actions of many hormones and drugs. The tissue specificity of the system is determined by the particular receptors that a cell expresses. Of the many receptors known to modulate adenylate cyclase activity, the best characterized and one of the most pharmacologically important is the beta-adrenergic receptor (beta AR). The pharmacologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
441
0
20

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,222 publications
(469 citation statements)
references
References 46 publications
8
441
0
20
Order By: Relevance
“…The widespread distribution of this mRNA has important implications with regard to the pharmacology of dopamine receptors and future prospects for the development of dopaminergic drugs which discriminate between receptors located in these different brain regions. In the case of other G-protein coupled receptors, it has been shown that when the same receptor genes are expressed in different cells, their antagonist pharmacology does not vary with respect to cell type [25,26,36], while agonist pharmacology varies with respect to both cell type and levels of receptor ( [28] and unpublished observations). Initial results with the cloned D2 receptors indicate that a similar relationship may hold since D2 receptors expressed in fibroblasts have the same affinity for antagonists and a lower affinity for agonists than do D2 receptors expressed by brain [30].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The widespread distribution of this mRNA has important implications with regard to the pharmacology of dopamine receptors and future prospects for the development of dopaminergic drugs which discriminate between receptors located in these different brain regions. In the case of other G-protein coupled receptors, it has been shown that when the same receptor genes are expressed in different cells, their antagonist pharmacology does not vary with respect to cell type [25,26,36], while agonist pharmacology varies with respect to both cell type and levels of receptor ( [28] and unpublished observations). Initial results with the cloned D2 receptors indicate that a similar relationship may hold since D2 receptors expressed in fibroblasts have the same affinity for antagonists and a lower affinity for agonists than do D2 receptors expressed by brain [30].…”
Section: Discussionmentioning
confidence: 97%
“…For example, several subtypes of muscarinic, serotonergic, and adrenergic receptors have now been cloned [19][20][21][22][23][24][25][26]. These receptor subtypes are expressed in distinct regions of the brain, and in the case of muscarinic receptors, different receptor gene products are expressed in presynaptic versus postsynaptic locations [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Among the explanations suggested to explain this outcome are their relatively small size, limited abundance, and hydrophobic nature. Hard won, some receptor protein sequence information eventually began to emerge that led to the successful cloning of cDNAs and genes for the opsins (Nathans & Hogness, 1983;Nathans & Hogness, 1984;Nathans et al, 1986) and the hamster beta2-adrenergic receptor (Dixon et al, 1986;Kobilka et al, 1987). Even with the limited number of examples available at the time molecular neurobiologists following these developments latched on immediately to the remarkable extent of amino acid sequence and structural conservation, in particular the presence of 7 putative transmembrane (TM) domains, shared by these integral membrane proteins.…”
Section: Discovery Of Vertebrate Trace Amine-associated Receptorsmentioning
confidence: 99%
“…myristate 13c~-acetate: PKC, protein kinase C; G. stimulatory guanine.nucleottde-blndlng proteifJ~ G~, inhibitory guanine-nucleo. tide-binding protein; Pl0 phospho-lnositides; [12~I]CYP, [t2Sllcyano-pindolol; CHW, Chinese hamster fibroblast; DMEM, Dulbecco's minimum Eagle's medium In sharp contrast, phorbol-ester treatment has been shown to induce a desensitization of the ~-adrenergicstimulated adenylyl cyclase in avian erythrocytes [14,15], Desensitization was accompanied by an increased phosphorylation of the ~a-adrenergic receptor (#2AR), It was susgested that PKC-mediated phosphorylation of the receptor could contribute to this desensitization, The mammalian B2AR receptor has been shown to be an in vitro substrata for PKC [20], and potential PKC phosphorylation sites are apparent m its primary structure [21,22]. Thus, questions arise concerning the role of the PKC-mediated phosphoryla, tion of the ~2AR in mammalian cellular systems.…”
Section: Introductionmentioning
confidence: 99%